Dongeng dan Seni Peran untuk Menumbuhkan Kemampuan 4C Bagi Siswa SD Negeri 2 Beringkit Belayu - Sartika, Lianda Dewi; Denafri, Bram (Education & Learning, 2024)
Storytelling and role-playing are learning methods capable of creating an enjoyable learning atmosphere while fostering students' skills. This study aims to analyze the implementation of storytelling and role-playing in enhancing critical, creative, communicative, and collaborative (4C) thinking skills among students at SDN 2 Beringkit Belayu. The study focuses on the effectiveness of these methods in building 4C competencies. A qualitative approach with a descriptive method was used, involving observations, interviews, and documentation of the learning process. The results indicate that storytelling facilitates imaginative conceptual understanding, while role-playing enhances students' active engagement and teamwork abilities. This study concludes that combining these two methods creates enjoyable, meaningful, and effective learning experiences in developing 4C skills. Further support is required to optimize this implementation through teacher training and adequate time allocation.